SUITABILITY OF THE KOZANI 'S AREA (NW MACEDONIA, GREECE) CARBONATE ROCKS FOR THE CEMENT INDUSTRY AND AS AGGREGATES IN CONSTRUCTIONS - Dagounaki, C.; Sikalidis, C.; Kassoli-Fournaraki, A.; Tsirambides, A. (Bulletin of the Geological Society of Greece, 2004)
The suitability of Kozani's broader area carbonate rocks for use in cement production and as aggregates, is studied in terms of their mineralogical, chemical and mechanical characteristics. The studied carbonate rocks belong to the Pelagonian zone and are represented mainly by pure limestones with subordinate dolomites and dolomitic limestones. Examination concerning their insoluble residue, organic matter and milling behavior, together with their mineralogical and chemical composition showed that all carbonate formations of Kozani's broader area, except the dolomitic ones, fulfill the requirements for use as raw material in the cement industry and all the carbonate formations meet the specifications for their use as aggregates in various constructions.